MANAGEMENT OF DIABETES, OBESITY AND GASTRIC DISORDERS USING THE â€˜INTEGRATED APPROACH' AT HEALTH TOTAL: A CASE STUDY - Mukerjee, Anjali (Asian Journal of Pharmaceutical and Clinical Research, 2018)
It has been found that high prevalence of hypertension and Type II diabetes is coincidental to obesity. A well-defined nutrition therapy is one of the most effective methods of managing and slowing down the rate of development of Type II diabetes, gastrointestinal (GI) problems, and hypertension. A healthy diet or plan for the above-mentioned complications should be one that is naturally rich in phytochemicals and low in glycemic index, bad fats, and excess calories. This case study deals with the benefits of an Integrated approachâ€ in the management of diabetes, hypertension, gastric disorders, and obesity. The integrated approachâ€ includes patient-specific nutritional therapy, ayurvedic herb support, vitamins and dietary supplements, stress management, and regular exercise. The subject in this study was a 39-year-old obese female with a clinical history of Type II diabetes, borderline hypertension, and GI issues. Apart from these she also complained of low immunity, low energy levels, and high levels of stress. During the 10-month treatment, significant weight loss was achieved along with normalization of blood sugar levels and steady lowering of blood pressure with subsequent improvement in gastric problems and improved energy levels. Hence, the case report aptly illustrates that an integrated approach can help, not only manage diabetes, hypertension, and obesity but also reduce drug dosage and significantly improve quality of life.